Nitazoxanide, a new drug candidate for the treatment of Middle East respiratory syndrome coronavirus - Jean-François Rossignol (Elsevier, 2016)
Summary: Nitazoxanide is a broad-spectrum antiviral agent undergoing clinical development for treatment of influenza and other viral respiratory infections. Nitazoxanide exhibits in vitro activity against Middle East respiratory syndrome coronavirus (MERS-CoV) and other coronaviruses, inhibiting expression of the viral N protein. Nitazoxanide also suppresses production of pro-inflammatory cytokines in peripheral blood mononuclear cells and suppresses interleukin 6 production in mice. Having been used extensively in clinical trials and in post-marketing experience, nitazoxanide is an attractive drug candidate for treatment of Middle East respiratory syndrome. Future research should include in vitro mechanism studies, animal models of MERS-CoV infection, clinical trials, including dose-ranging trials, and evaluation of combination therapy with other potential MERS-CoV antivirals. Keywords: Nitazoxanide, Coronavirus, MERS-CoV, Treatment